Uganda Systematic Country Diagnostic : Boosting Inclusive Growth and Accelerating Poverty Reduction - World Bank Group (World Bank, Washington, DC, 2015)
After a destructive civil war and extreme political instability, Uganda began its reconstruction process in 1987. Within the enabling environment of macroeconomic stability, most of the progress on the twin goals was attributable to higher agricultural incomes. Poverty reduction among households primarily engaged in agriculture accounted for 53 percent of the reduction in poverty from 2006 to 2010 and 77 percent of the reduction in poverty from 2010 to 2013. Despite significant progress on the twin goals, vulnerability to poverty in Uganda is high and the sparse social safety nets and limited access to finance have provided little protection. Change in economic and social policies is required to prevent a slowdown in poverty reduction and an increase in vulnerability. In this context, a comprehensive framework based on the three interrelated blocks of growth, inclusion, and sustainability has been used to identify the challenges to and opportunities for ending poverty and boosting shared prosperity. The first block emphasizes the development of a competitive and resilient private sector to lead the growth process by adequately capitalizing on all the available opportunities. The second block, complementary to the first one, reinforces the need to ensure a fair distribution of the growth dividend across all Ugandans, especially those living in the north and the east, by providing them with access to social and infrastructure services so that they can increase their productive capacity and income generating opportunities. The third block emphasizes the need to undertake the inclusive growth process in a fiscally, socially, and environmentally sustainable manner.